2011
DOI: 10.1007/978-3-642-19715-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Age, Gender and Culture as Correlates of Use of Knowledge Management Systems in Makerere University

Abstract: Abstract. The purpose of the study was to establish which of (i) age (ii) gender and (iii) organizational culture is a correlate of use of knowledge management systems (KMS) among teachers, senior administrators and postgraduate students in Makerere University. The study was a co-relational and cross-sectional survey biased to the quantitative approach, involving 444 respondents from the University, from whom primary data were collected using a self-administered questionnaire, and analysed using summary statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…The study found no gender difference between female and male participants concerning sports knowledge management in achieving a competitive advantage. The present study results are also consistent with the findings of (24). This result contrasts all of the other studies that indicated differences regarding knowledge management and achieving a competitive advantage in favor of males.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study found no gender difference between female and male participants concerning sports knowledge management in achieving a competitive advantage. The present study results are also consistent with the findings of (24). This result contrasts all of the other studies that indicated differences regarding knowledge management and achieving a competitive advantage in favor of males.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, gender differences, as shown in the study (23), found that differences regarding knowledge management and achieving a competitive advantage is in favor of males. On the other hand, (24) found that both males and females are equally at KM. Furthermore, (25) reported that gender plays a significant role in social and competitive preferences.…”
Section: Introductionmentioning
confidence: 96%
“…It also shows that there is no significant difference in statistics anxiety between the male and female respondents. Multivariate regression analysis takes into account the simultaneous relationship between academic procrastination, perfectionism, gender and statistics anxiety (Bakkabulindi and Sekabembe, 2010). The results from multiple regression analysis are shown in Table 7.…”
Section: Discussionmentioning
confidence: 99%
“…Studies relating OC to innovation adoption can be found (e.g. Bakkabulindi & Sekabembe, 2010). Studies in support of the hypothesis aside, there are studies that totally dismissed the hypothesis to the effect that OC is a correlate of innovation adoption (e.g.…”
Section: Organisational Culture As a Correlate Of Adoption Of Innovatmentioning
confidence: 99%